NOVEL IN SILICO APPROACH OF ANTICANCER ACTIVITY BY INHIBITING HEMOPEXIN PROTEINS WITH INDIGOFERA ASPALATHOIDESPLANT CONSTITUENTS AT ACTIVE SITE - L, Krishnasamy; M, Masilamani selvam; K, Jayanthi (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The aim of the study was to investigate the anti-cancer activity using the phytoconstituents of Indigofera aspalathoides. Methods: The plant extract has been largely used as cell proliferation inhibitors. In this study, specific phytoconstituent has been targeted towards matrix metalloproteinases (MMPs). Results: MMPs are group of proteinases that are associated with cell invasion inhibition and also inhibit proliferation. The C-terminal domain of MMPs mimics the serum protein hemopexin (HPX). According to various literatures, a reason for the failure of MMP as anti-cancer agent is the presence of this HPX binding at the active site. Conclusion: A novel approach was carried to inhibit this binding by Carotal, (-)-Spathulenol, Tau.-Cadinol proteins from the plant I. aspalathoides. Â Keywords: Hemopexin, Matrix metalloproteinase, Indigofera aspalathoides, Molecular docking, Carotal, (-)-Spathulenol, Tau.-Cadinol.